Drug mechanism‐of‐action discovery through the integration of pharmacological and CRISPR screens. Issue 7 (6th July 2020) - Gonçalves, Emanuel; Segura‐Cabrera, Aldo; Pacini, Clare; Picco, Gabriele; Behan, Fiona M; Jaaks, Patricia; Coker, Elizabeth A; van der Meer, Donny; Barthorpe, Andrew; Lightfoot, Howard; Mironenko, Tatiana; Beck, Alexandra; et al.
Abstract: Low success rates during drug development are due, in part, to the difficulty of defining drug mechanism‐of‐action and molecular markers of therapeutic activity. Here, we integrated 199, 219 drug sensitivity measurements for 397 unique anti‐cancer drugs with genome‐wide CRISPR loss‐of‐function screens in 484 cell lines to systematically investigate cellular drug mechanism‐of‐action. We observed an enrichment for positive associations between the profile of drug sensitivity and knockout of a drug's nominal target, and by leveraging protein–protein networks, we identified pathways underpinning drug sensitivity. This revealed an unappreciated positive association between mitochondrial E3 ubiquitin–protein ligase MARCH5 dependency and sensitivity to MCL1 inhibitors in breast cancer cell lines. We also estimated drug on‐target and off‐target activity, informing on specificity, potency and toxicity. Linking drug and gene dependency together with genomic data sets uncovered contexts in which molecular networks when perturbed mediate cancer cell loss‐of‐fitness and thereby provide independent and orthogonal evidence of biomarkers for drug development. This study illustrates how integrating cell line drug sensitivity with CRISPR loss‐of‐function screens can elucidate mechanism‐of‐action to advance drug development. Synopsis: This study integrates pharmacological and CRISPR screens in 484 cancer cell lines to systematically investigate anticancer drug mechanism of action, yielding insights into the genetic contexts and cellular networks underpinning drug response. CRISPR screens reveal important aspects of drug mechanism‐of‐action, specifically in the context of cellular activity, isoform specificity, off‐target and polypharmacological effects. By leveraging protein interaction networks that underlie drug‐responses, novel drug‐target interactions involving anti‐apoptotic MCL1 inhibitors are identified. Improved pharmacogenomic biomarker discovery using two independent and orthogonal cell viability screens. Abstract : This study integrates pharmacological and CRISPR screens in 484 cancer cell lines to systematically investigate anticancer drug mechanism of action, yielding insights into the genetic contexts and cellular networks underpinning drug response.